2008
DOI: 10.1210/me.2007-0350
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of in Situ Estrogen Synthesis by Proline-, Glutamic Acid-, and Leucine-Rich Protein-1: Potential Estrogen Receptor Autocrine Signaling Loop in Breast Cancer Cells

Abstract: In situ estrogen synthesis is implicated in tumor cell proliferation through autocrine or paracrine mechanisms especially in postmenopausal women. Several recent studies demonstrated activity of aromatase, an enzyme that plays a critical role in estrogen synthesis in breast tumors. Proline-, glutamic acid-, and leucine-rich protein-1 (PELP1/MNAR) is an estrogen receptor (ER) coregulator, and its expression is deregulated in breast tumors. In this study, we examined whether PELP1 promotes tumor growth by promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 56 publications
2
40
0
1
Order By: Relevance
“…PELP1 also promotes local estrogen synthesis via Src kinase pathway facilitating growth of tumors in an autocrine manner [31]. Therefore, we hypothesized that PELP1 driven tumors can be therapeutically targeted using dasatinib and performed a proof of principle experiment using a post-menopausal xenograft model.…”
Section: Resultsmentioning
confidence: 99%
“…PELP1 also promotes local estrogen synthesis via Src kinase pathway facilitating growth of tumors in an autocrine manner [31]. Therefore, we hypothesized that PELP1 driven tumors can be therapeutically targeted using dasatinib and performed a proof of principle experiment using a post-menopausal xenograft model.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of PDZK1 decrease in tissues from women older than 55 years of age. It is tempting to speculate that this result may be linked to the decreasing levels of plasma estrogen (19,20). This potential connection becomes even more important in light of the report that intratumoral estrogen levels could reach levels as high as 20 times that detected in the plasma of affected individuals (21).…”
Section: Discussionmentioning
confidence: 98%
“…We failed to see any significant differences in the tumor latency in multiparous animals compared to nulliparous animals. Since our earlier studies showed that PELP1 deregulation induces local E2 synthesis via aromatase regulation (26) and such findings may explain to some extent the lack of exacerbate phenotype in PELP1 Tg multiparous animals, however, future studies are needed. Our ongoing studies will address the role of local estrogen in PELP1 mediated tumorgenesis and also test the effect of PELP1 overexpression on various stages of development of mammary gland.…”
Section: Discussionmentioning
confidence: 99%